The relationship between leader support, staff influence over decision making, work pressure and patient satisfaction: a cross-sectional analysis of NHS datasets in England - Thomas H R West; Pascale Daher; Jeremy F Dawson; Joanne Lyubovnikova; Sandra C Buttigieg; Michael A West (BMJ Open)
Objective To explore the relationships between leader support, staff influence over decisions, work pressure and patient satisfaction.Design A cross-sectional study of large National Health Service (NHS) datasets in England in 2010.Setting and participants 158 NHS acute hospital trusts in England (n=63 156) from all staff groups.Primary and secondary outcome measures Survey data measuring leader support, staff influence over decision making, staff work pressure and objective outcome data measuring patient satisfaction.Results Multilevel serial mediation analysis showed a significantly positive association between leader support and staff influence over decisions (B=0.74, SE=0.07, p<0.01). Furthermore, staff influence over decisions showed a negative association with staff work pressure (B=−0.84, SE=0.41, p<0.05) which in turn was negatively linked to patient satisfaction (B=−17.50, SE=4.34, p<0.01). Serial mediation showed a positive indirect effect of leader support on patient satisfaction via staff influence over decisions and work pressure (B=10.96, SE=5.55, p<0.05).Conclusions and implications Our results provide evidence that leader support influences patient satisfaction through shaping staff experience, particularly staff influence over decisions and work pressure. Patients’ care is dependent on the health, well-being, and effectiveness of the NHS workforce. That, in turn, is determined by the extent to which leaders are supportive in ensuring that work environments are managed in a way which protects the well-being of staff.